Morphological and physico-chemical Properties of Denuded Forest Soils under the Influence of Oilpalm Plantation - George Jose (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
A study has been made on the soils of Yeroor estate of Oil palm India Ltd., Bharatheepuram, Quilon District, Kerala State with a view to assess the effect of oil palm plantation on their morphological, physical and chemical characters and the mineralogical set up of the Clay fraction. Four profile pits were dug in each of the four age group plantations, viz., the 4, 8, 12 and 16 year old oil palm plantations and the adjacent denuded area without plantations, and morphological studies carried out. Soil samples from three layers, viz., surface (S), subsurface (SS1) and subsoil (SS2) were studied for their physic - chemical properties. The clay fraction of the soil from the upper two layers of the representative profiles of the denuded forest area and the oil palm plantations was separated and analyses for its mineralogical set up. The study revealed that in all the layers of denuded forest area, as well as in the plantations, the soils contained appreciable quantities of gravel. Distribution of gravel in general, showed an increasing trend with depth. There was significant variation in the properties of silt and clay with the age of the plantation and also with depth. The bulk density and particle density increased with depth in the profiles. The bulk density as well as particle density was highest and volume expansion was the lowest in the 8 year old plantation which is probably caused by a fundamental difference in the chemical nature of this plantation from that of the other plantations. The highest CEC was observed in the soils of denuded forest containing the highest organic matter. The decrease in CEC with the age of plantation and depth of soils may be attributed to a corresponding decrease in organic matter. The soils of the denuded forest were slightly more acidic than the soils of plantations due to the higher content of organic matter. Soils of the 12 year plantation had the highest pH and correspondingly the lime requirement was lowest for these soils. The pH was found to decrease with depth. The CEC and the lime requirement also showed a decrease with depth in the profiles. The decrease in CEC with depth explains the downward decrease of the lime requirement. Both total and available nitrogen and C/N ration decreased with the age of the plantation and with depth. A similar trend was shown by organic carbon also. Total phosphorus showed variation with the age of plantation but the variation did not show any regular pattern. Hence it is difficult to attribute it to the effect of the growth of palms. The second layer of all profiles contained more of total phosphorous. This may be due to the removal of phosphorous from the surface layer by annuals and from the deeper layer by the deep rooted perennials leaving the intermediate layer enriched with respect to total phosphorous. Available phosphorous remained constant in all the profiles. However in the 16 year old plantation there was a sudden decrease in its value which might be due to plant removal. Available phosphorous decreased with depth of soil in all the profiles. As the organic matter and consequently the organic forms of phosphorous have been decreasing with depth, there has been a corresponding decrease in available phosphorous also. Total potassium remained somewhat constant irrespective of the age of the plantation and there was a slight accumulation of total potassium in the intermediate layer. Exchangeable potassium varied in an irregular manner with the age of the plantation but with depth it decreased steadily. Total calcium and magnesium also showed no regularity in variation with the age of the plantations. Both total calcium and magnesium were highest in the surface layer. Exchangeable calcium and magnesium varied irregularly with the age of the plantation, but both of these elements decreased steadly with depth of the soil. Total iron and aluminium were lowest in the 8 year old plantation. Total iron increased steadily with depth down the profile, whereas total aluminium showed a slight decrease in the second layer and then an accumulation in the third layer of the profile. The variation in the exchangeable iron and aluminium with the age of the plantation did not show any regular pattern. However there was a steady decrease in both exchangeable iron and aluminium with depth. Analytical results of the clay indicate that the clay is predominantly of the 1:1 type. The chemical character of the clay from various soils did not show any regular variation with the age of plantation.